The elusive global burden of dengue - Wilder-Smith, Annelies (2016)
Dengue has emerged in the past two decades as a rapidly growing and widespread public health problem, with over half of the world's countries and people now at risk.1 In new estimates from the Global Burden of Disease study published in The Lancet Infectious Diseases, Jeffrey Stanaway and colleagues2 suggest that dengue incidence has increased six-fold from 1990 to 2013, accompanied by much flatter mortality trends. Dengue is still regarded as a neglected disease,3 yet its incidence is increasing at an alarming rate, by contrast with declines in other neglected diseases.